Evaluation of interactive effects of phosphorus-32 and copper on marine and freshwater bivalve mollusks. (3rd June 2022) - Vernon, Emily L.; Moore, Michael N.; Bean, Tim P.; Jha, Awadhesh N.
Abstract: Purpose: Contaminants seldom occur in isolation in the aquatic environment. While pollution of coastal and inland water bodies has received considerable attention to date, there is limited information on potential interactive effects between radionuclides and metals. Whether by accidental or controlled release, such contaminants co-exist in aquatic ecosystems and can pose an enhanced threat to biota. Using a range of biological responses, the study aimed to evaluate relative interactive effects on representative freshwater and marine bivalve species. Methods: An integrated, multi-biomarker approach was adopted to investigate response to copper (Cu, 18 μ g L −1 ), a known environmentally relevant genotoxic metal and differing concentrations of phosphorus-32 ( 32 P; 0.1 and 1 mGy d −1 ), alone and in combination in marine ( Mytilus galloprovincialis ) and freshwater ( Dreissena polymorpha ) mussels. Genetic and molecular biomarkers were determined post-exposure and included DNA damage (as measured by the comet assay), micronuclei (MN) formation, γ-H2AX foci induction and the expression of key stress-related genes (i.e. hsp70/90, sod, cat, gst ). Results: Overall, using a tissue-specific (i.e. gill and digestive gland) approach, genotoxic response was reflective of exposures where Cu had a slight additive effect on 32 P-induced damage across the species (but not all), cell types and dose rates. Multivariate analysis found significant correlations between comet and γ-H2AX assays, across both the tissues. Transcriptional expression of selected genes were generally unaltered in response to contaminant exposures, independent of species or tissues. Conclusions: Our study is the first to explore the interactive effects of ionizing radiation (IR) and Cu on two bivalve species representing two ecological habitats. The complexity of IR-metal interactions demonstrate that extrapolation of findings obtained from single stressor studies into field conditions could be misrepresentative of real-world environments. In turn, environmental protective strategies deemed suitable in protecting biota from a single, isolated stressor may not be wholly adequate. Highlights: Adoption of an integrated, multi-biomarker approach in two bivalve species. Toxicity of combined mixtures of 32 P and Cu compared. Cu induced additive effects with 32 P in the tissues. DNA damage and DDR showed strong correlations. Multiple stressors should be considered in assessing the impact of ionizing radiations. Abstract : Abbreviations: μ g: microgram; γ-H2AX: Gamma Histone 2AX; 60 Co: Cobalt 60; 137 Cs: Cesium 137; 3 H: Tritium; 32 P: Phosphorus 32; 32 S: Sulfur 32; 90 Sr: Strontium 90; ACT: Actin; ATP: Adenosine triphosphate; Bq: Becquerel; BHA: Butylated hydroxyanisole; CAT: Catalase; cDna: Complimentary DNA; CPM: Counts per minute; Cq: Threshold cycle; Cu: Copper; DAPI: 4′:6-diamidino-2-phenylindole dihydrochloride; DDR: DNA damage response; DG: Digestive gland; DI: Deionized water; DO: Dissolved oxygen; DOC: Dissolved organic carbon; DP: Dreissena polymorpha ; DSB: Double strand break; EF1: Elongation factor 1; ERICA: Environmental Risk from Ionizing Contaminants: Assessment and Management; GST: Glutathione-S-Transferase; HCl: Hydrochloric acid; HSP: Heat Shock Protein; ICP-MS: Inductively coupled plasma mass spectrometry; IR: Ionizing radiation; LET: Linear energy transfer; LMA: Low melting point agarose; LSC: Liquid Scintillation Counting; MBq: Mega Becquerel; MG: Mytilus galloprovincialis ; mGy: Milligray; MN: Micronuclei; MOA: Mechanism of action; MT-10: Metallothionein 10; NPP: Nuclear power plant; PCA: Principal component analysis; PCR: Polymerase chain reaction; qPCR: Quantitative PCR; RER: Relative expression ratio; ROS: Reactive oxygen species; SOD: Superoxide Dismutase; SSB: Single strand break; TBHQ: Tertiary-butyl hydroquinone